(untitled) (Fiep Bulletin - online, 2014)
This article portrays John Andrews’ personal view on some of the changes in Physical Education over the past sixty years. Using his own story as a guideline, John Andrew leads the reader through the changes experienced by Physical Education and Sports throughout the years.His story begins in primary school, where the idea of organised physical activity was that of exercises led by the class teacher, in the classroom. At the preparatory school he witnessed the replacement of ex-army Physical Training instructor by physical education specialists. A professional with a one-year postgraduate PE qualification would take over the teaching position some time later.By the year of 1953, John Andrews applied to a new University Degree course at the University of Birmingham, which pursued to the students a General Degree in two major subject departments. At the end of three years, that course would be the first PE intake to receive classified Honours Degrees.After three years in the military service with the Royal Air Force, John Andrew took a post at Roman Hill Secondary Modern School. The programme he built up at that time, which combined the skills and interests of many members of staff, was featured at a Physical Education Association national conference and recorded for posterity in a book written by Gerald Murray. In 1964, at St. Paul’s Men’s Teacher Training College in Cheltenham, John Andrew experienced the golden age of teacher preparation.At that institution, John Andrews also lived a civilised and respectful period of co-operation with Bristol University followed by great external pressures and internal bureaucracy caused by a hectic period of course validation ensued by the Council for National Academic Awards. In the late 1960’s, he was a member of one of the groups that drafted the first statutes of the new British Council of Physical Education. His experience in the attempt to unite the various professional groups in and around Physical Education "to speak with one voice” played an important part in his preparation for his future work in the world of international organisations of physical education and sport.After writing the official English version of the 1970 FIEP World Manifesto, John Andrew took charge of the English text of the FIEP Bulletin in 1972. Twelve years later he took on the role of FIEP President and during his four presidential mandates, FIEP achieved a considerable increase in its worldwide programme of activities, including a long collaboration with the Arab Sports Confederation. One of John Andrews’ successful administration landmarks took place when FIEP was once again an “IOC Recognised Organisation” and part of the wider Olympic family, which entitled it to become the recipient of annual grant aid. Another remarkable fact in his administration is the fact that, for the past eighteen years, the largest regular gathering of physical educationists in South America has been the FIEP Congress and Courses organised in Foz do Iguacu, Brazil, every January. President John Andrew attended most of these events, which often bring together up to 3000 participants.In January 2000, he passed the Presidency of FIEP to Dr. Manoel Tubino, and was elected FIEP’s Life President of Honour.